2018
DOI: 10.1371/journal.pone.0202330
|View full text |Cite|
|
Sign up to set email alerts
|

Parent reports of adolescents and young adults perceived to show signs of a rapid onset of gender dysphoria

Abstract: PurposeIn on-line forums, parents have been reporting that their children are experiencing what is described here as “rapid-onset gender dysphoria,” appearing for the first time during puberty or even after its completion. The onset of gender dysphoria seemed to occur in the context of belonging to a peer group where one, multiple, or even all of the friends have become gender dysphoric and transgender-identified during the same timeframe. Parents also report that their children exhibited an increase in social… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
155
1
14

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 237 publications
(225 citation statements)
references
References 59 publications
5
155
1
14
Order By: Relevance
“…Principles of research methods necessitate that a study's design must be appropriate to the aims of the study and the context of the phenomenon (Cozby, 2012;Ruane, 2005). In Littman's case, the majority of methodological and design issues stem from the use of a pathologizing framework and language of pathology to conceive, describe, and theorize the phenomenon as tantamount to both an infectious disease ("cluster outbreaks of gender dysphoria") and a disorder (e.g., "eating disorders and anorexia nervosa") (Littman, 2018). Consequentially, the study design and interpretation of the results are framed with this pathology framework.…”
Section: Framework and Premisementioning
confidence: 99%
See 3 more Smart Citations
“…Principles of research methods necessitate that a study's design must be appropriate to the aims of the study and the context of the phenomenon (Cozby, 2012;Ruane, 2005). In Littman's case, the majority of methodological and design issues stem from the use of a pathologizing framework and language of pathology to conceive, describe, and theorize the phenomenon as tantamount to both an infectious disease ("cluster outbreaks of gender dysphoria") and a disorder (e.g., "eating disorders and anorexia nervosa") (Littman, 2018). Consequentially, the study design and interpretation of the results are framed with this pathology framework.…”
Section: Framework and Premisementioning
confidence: 99%
“…Specifically, the article begins with the premise of conceptualizing gender dysphoria and trans identification as partly a consequence of "social and peer contagion" that "spreads of affect or behaviors through a popula-tion… [and] where an individual and peer mutually influence each other in a way that promotes emotions and behaviors that can potentially undermine their own development or harm others" (Littman, 2018). The article continues to pathologize gender dysphoria and affirmation of trans identification through social network peers and online environments as an example of "deviancy training," and describing it as an unhealthy pattern of reinforcement with trans-identified peers and linking it with a behavior that is "deceiving parents and doctors" (Littman, 2018). The pathologizing lens used by Littman to study this gender dysphoria-related phenomenon speaks to the researcher's a priori bias that is manifested in the construction of measurements and methodologies deliberately chosen to investigate this phenomenon.…”
Section: Framework and Premisementioning
confidence: 99%
See 2 more Smart Citations
“…Similar pressure from LGBT activists is related to the publication of Dr. Lisa Littman, an assistant professor of behavioral and social sciences at Brown University. Dr. Littman studied the reasons for the surge of "rapid-onset gender dysphoria" among youth and concluded that their sudden drive to transition might spread through peers and may be a harmful coping mechanism [70]. Before declaring themselves transgenders, teenagers watched videos about transition, communicated with transgender people on social networks and read transgender resources.…”
Section: Harassment Of Dissentersmentioning
confidence: 99%